2016
DOI: 10.1080/14767058.2016.1220528
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of short cervix between 20 and 24 weeks of gestation and vaginal progesterone for prolonging of gestation

Abstract: The rate of short cervical length was less than expected. Vaginal progesterone is efficacious for the prolonging of gestation in women with a cervical length of 10-20 mm in the mid-trimester for a singleton gestation and nulliparous women. For a cervical length of 20-25 mm in the mid trimester, vaginal progesterone compared with bed rest did not prolong pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…One limitation of progesterone therapy is that it is applicable to only a small percentage of pregnant women (primarily those with a shortened cervix and those with a history of previous sPTB), so its net benefits on a population basis are limited 4, 42, 48 . Nevertheless, several studies have now confirmed the feasibility of conducting population-based cervical screening programs 28, 34, 49, 50 and have concluded that the cost-effectiveness of such programs combined with progesterone therapy is favourable 49, 5154 , although they would clearly be improved if the effectiveness of interventions could be increased 55 .…”
Section: Recent Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…One limitation of progesterone therapy is that it is applicable to only a small percentage of pregnant women (primarily those with a shortened cervix and those with a history of previous sPTB), so its net benefits on a population basis are limited 4, 42, 48 . Nevertheless, several studies have now confirmed the feasibility of conducting population-based cervical screening programs 28, 34, 49, 50 and have concluded that the cost-effectiveness of such programs combined with progesterone therapy is favourable 49, 5154 , although they would clearly be improved if the effectiveness of interventions could be increased 55 .…”
Section: Recent Advancesmentioning
confidence: 99%
“…Several lines of evidence suggest that inflammation in the cervix is required for effective vaginal progesterone treatment, which appears to work at least in part through an anti-inflammatory mechanism 45, 48, 5658 . Markers of cervical inflammation could, therefore, be employed to target therapy to those at highest risk 59, 60 .…”
Section: Recent Advancesmentioning
confidence: 99%
“…A number of interventions have been shown to significantly decrease the rate of spontaneous preterm birth (sPTB) including specialist antenatal clinics for women at high risk of PTB [6]; cervical cerclage for women with a previous sPTB and/or a short cervix (< 25 mm) [7,8] and vaginal progesterone for women with cervical length < 25 mm [9][10][11][12][13]. Progesterone decreases uterine contractility through inhibition of production of prostaglandins in the myometrium [14] and has been shown to be important in maintaining a pregnancy until term [15].…”
Section: Introductionmentioning
confidence: 99%
“…A number of interventions have been shown to signi cantly decrease the rate of spontaneous preterm birth (sPTB) including: specialist antenatal clinics for women at high risk of PTB(6); cervical cerclage for women with a previous sPTB and/or a short cervix (< 25 mm) (7,8) and vaginal progesterone for women with cervical length < 25 mm (11)(12)(13)(14)(15). Progesterone decreases uterine contractility through inhibition of production of prostaglandins in the myometrium (9) and has been shown to be important in maintaining a pregnancy until term (10).…”
Section: Introductionmentioning
confidence: 99%
“…This IPD suggested that vaginal progesterone is still bene cial even in nulliparous women with only a short cervix as a risk factor (8). As only 5.8-7.3% of high risk women (11,12), and 0.45-1.68% in unselected populations (13)(14)(15) have a short cervix at mid gestation, the number of women who bene t from progesterone is relatively low. It is currently unclear whether vaginal progesterone would be of bene t to the other highrisk women with a normal mid-gestation cervical length (> 25 mm).…”
Section: Introductionmentioning
confidence: 99%